2021
DOI: 10.1002/jbm4.10582
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Breast Cancer: Mechanistic Update

Abstract: The presence of the vitamin D receptor (VDR) in mammary gland and breast cancer has long been recognized, and multiple preclinical studies have demonstrated that its ligand, 1,25-dihydroxyvitamin D (1,25D), modulates normal mammary gland development and inhibits growth of breast tumors in animal models. Vitamin D deficiency is common in breast cancer patients, and some evidence suggests that low vitamin D status enhances the risk for disease development or progression. Although many 1,25Dresponsive targets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…In colon carcinoma cells, 1,25-(OH) 2 D 3 upregulates an array of intercellular adhesion molecules that are constituents of adherens junctions and tight junctions, including E-cadherin, occludin, claudin-2 and -12, and ZO-1 and -2 [ 125 , 131 ]. As mentioned by JoEllen Welsh in an excellent recent review [ 187 ], breast cancer heterogeneity is reflected in available model systems of this disease, including human breast cancer cell lines. These differ in the expression of VDR and other hormone receptors and in their global gene expression profile and phenotype.…”
Section: Mechanisms Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In colon carcinoma cells, 1,25-(OH) 2 D 3 upregulates an array of intercellular adhesion molecules that are constituents of adherens junctions and tight junctions, including E-cadherin, occludin, claudin-2 and -12, and ZO-1 and -2 [ 125 , 131 ]. As mentioned by JoEllen Welsh in an excellent recent review [ 187 ], breast cancer heterogeneity is reflected in available model systems of this disease, including human breast cancer cell lines. These differ in the expression of VDR and other hormone receptors and in their global gene expression profile and phenotype.…”
Section: Mechanisms Introductionmentioning
confidence: 99%
“…This in vivo action is difficult to dissect and probably results from a variable combination of mechanisms in the distinct systems that were assayed, including the inhibition of tumor cell growth, EMT, invasiveness, angiogenesis, and metastasis. Importantly, as occurs in cultured cancer cells, vitamin D antitumor action is mostly independent of TP53 gene status [ 119 , 187 ].…”
Section: Mechanisms Introductionmentioning
confidence: 99%
“…On the other hand, calcitriol, the most active vitamin D metabolite, exerts pro-differentiating and antiproliferative effects in breast cancer [ 14 ], and has shown an anti-EMT effect in epithelial cells through inhibiting the PI3K/Akt/β-catenin pathway [ 15 ]. Also, calcitriol exerts potent anti-inflammatory activity, partially through downregulating JAK-STAT pathway activation and inflammatory cytokine production, processes known to be involved in carcinogenesis and VM [ 16 , 17 ]; however, calcitriol’s effects upon VM has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that higher vitamin D levels might reduce the risk of developing breast cancer [ 14 , 27 , 28 , 29 , 30 ]. Animal studies have also shown that vitamin D deficiency might play a role in primary tumor growth and the development of metastases in breast cancer cells [ 31 ], and an association between low vitamin D receptor expression and occurrence of more aggressive breast cancer has been seen [ 32 ].…”
Section: Discussionmentioning
confidence: 99%